Enhancement of Lasing Emission in the Metalliccoated Microsphere Cavity Based on Er-doped Silica Glasses - Hoi, Pham Van; Anh, Nguyen The; Trang, Nguyen Thi Thu; Thang, Le Huu; An, Nguyen Van (Communications in Physics, 2015)
In this paper, we present a review of enhancement and wavelength shift of abnormal upconversion green light emission from erbium ions doped in silica with narrow linewidth in the metallic-coated microsphere cavity. Although the phenomenon of the 537 nm- green light emission is not yet understood, its enhancement of several orders of magnitude seems to be due to the excitation of plasmons. The metallic-coated microsphere cavity has led to the lowest threshold so far observed in microsphere cavity lasers from 0.2 mW to 60 nW. By combining microcavity and surface plasmonic enhancement effect the researchers have created a new kind of photonic devices